2020
DOI: 10.1111/hsc.13198
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of transition from children's to adult's healthcare services for young people with a neurodevelopmental condition

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…However, many young people with neurodevelopmental disabilities and their carers worry about meeting eligibility criteria for adult mental health services. 12 Joint transition planning between child and adult mental health services, primary and community care might help to reduce the need for unplanned hospital care for young people with LD/ASD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many young people with neurodevelopmental disabilities and their carers worry about meeting eligibility criteria for adult mental health services. 12 Joint transition planning between child and adult mental health services, primary and community care might help to reduce the need for unplanned hospital care for young people with LD/ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Specialist adult care is more likely to be fragmented, with services being system or condition focussed, longer waiting times and higher thresholds for accessing services. 11 , 12 Parents often report becoming advocates to help their young person navigate the transition to adult care. 11 , 12 , 13 , 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age range of patients was between 14 and 29 years, and they enrolled at different stages of transition: 45 before transition, 247 during transition and 17 after transition, while 79 had been discharged from services and 21 had been disengaged and then had been reinserted in adult services. ( Shanahan et al, 2021;Swift et al, 2013). In particular, adult services were hard to reach because of strict eligibility criteria to have access (i.e., age, symptoms severity and comorbidities), and many refused referral; more than a half of young patients refused by adult services remained in charge of child services or discharged from child services seeking help in private practice (Eklund et al, 2016;Tatlow-Golden et al, 2018).…”
Section: Patients' Experience: Barriers and Suggestionsmentioning
confidence: 99%
“…Transition to adult services is recognized to be difficult for young people and their families, with some of the problems identified being poor communication between services (Gauthier-Boudreault et al,2021;Culnane et al,2020;Brown et al, 2019;Franklin et al, 2019), a relative lack of appropriate adult services (Piccoli et al, 2020;Culnane et al, 2020; (Information about the authors can be found at the end of this article.) Shanahan et al, 2020), difficulty in accessing adult services due to restrictive access criteria (Young-Southward et al, 2017;Belling et al, 2014;Barron et al, 2013) and loss of integrated health care (Brown et al, 2019). Sloper et al (2010) in their wide-ranging study of the impact of transition teams on the effectiveness of transition for young people found a high level of unmet need including factors impacting on mental health.…”
Section: Introductionmentioning
confidence: 99%